"This phone saved my life": Older persons' experiences and appraisals of an mHealth intervention aimed at addressing loneliness. Issue 2 (4th March 2019) - Jarvis, Mary Ann; Chipps, Jennifer; Padmanabhanunni, Anita
Abstract : This qualitative study aimed to explore older persons' experiences and appraisals of the utility of an mHealth intervention for reducing their sense of loneliness. Participants (n = 13; 86.42% females; age range 65 to 87 years) received training in the use of a smartphone and a social networking application (WhatsApp). Following the intervention, they completed a focus group discussion. For data triangulation, participants shared their social media postings. Content analysis of the focus group discussion and social media data indicated that the mobile device was used to mitigate perceptions of loneliness and isolation, thus facilitating social network building, enhancing self-efficacy, and improving cognitive flexibility. Mobile phones and a social networking application appear to reduce loneliness experienced by the elderly.